A novel group decision-making method by P-robust fuzzy DEA credibility constraint for welding process selection. Issue 1 (1st January 2020) - Wardana, Rahmad Wisnu; Masudin, Ilyas; Restuputri, Dian Palupi
Abstract: The selection of the welding process is a matter of decision-making involving a variety of information according to the type of product.Accordingly, the vast information will significantly enhance the decision-making process. A combined p-robust technique, fuzzy credibility constrained programming and data envelopment analysis (DEA) are proposed to select the welding process for repairing the shredder hammer. The p-robust technique has regret value to control relative regret of data, and fuzzy credibility constraint programming has confidence level to satisfy chance constraints. In addition, the proposed approach is able to handle fuzzy input data and fuzzy output data to uncertainty data. The proposed method is used to investigate which welding process is best based on two cases. Three welding processes are analyzed for the first case that focuses on manual welding process, and four welding processes are investigated for the second case that focuses on automatic welding process. According to the results, increasing the credibility level would also increase the discrimination power of the proposed approach, so the ranking of DMUs could be seen easily.